Error Analysis of Chinese Word Order of Indonesian Students - Yetty Go (Bina Nusantara University, 2014)
This study used comparative analysis to understand the similarities and differences of basic structure adverbial word order between Chinese language and Bahasa Indonesia. This study also analyzed Indonesian student’s common errors in learning adverbial word order, and the result found that student’s common error are adverbial clause of time, place, and preposition as adverbial word order. This research suggests teachers must emphasize the differences in the basic word order between Chinese language and bahasa Indonesia language first, then teach the differences of adverbial word. Teachers shoud encourage students to practice listening, speaking, reading, and writing skills, so they can overcome the differences between Chineseand Indonesia language, and reduce the errors in learning.